Valorization of agro-industrial waste through chemical and microbiological approaches - Figueira, Diogo Rendeiro (2017)
The main objective of this thesis was to use grape pomace (GP) as a source of carbohydrates for yeast growth and subsequent production of lipids, or carotenoids, thereby achieving the valorization of a very important agro-industrial residue. To that effect, subcritical water (SBW) technology was used as a treatment to overcome the resilience of the GP lignocellulosic matrix, and depolymerize it into more elementary structures. Experiments were conducted on the growth of yeast strains on the GP extract resulting from the carbohydrate-rich liquor generated during SBW treatment, under conditions conducive to lipid accumulation and carotenoid production. SBW extraction / hydrolysis experiments were carried out at a constant pressure of 70 bar, a water flow rate of 10 mL/min, and maximum temperatures between 190°C and 240 °C. Two temperature programs were used, namely one in which temperature was increased continuously to the target temperature, and another consisting of a series of steps, each step consisting of a ramp followed by a plateau, aiming at the fractionation of GP into extractives (plateau at 130 ºC), hemicellulose constituents (plateau at 190 ºC), and glucose or gluco-oligosaccharides from cellulose (plateau at 240 ºC). The best results were obtained in a plateau-type assay reaching 240 ºC. At these conditions, the extraction / hydrolysis efficiency of the SBW treatment of GP was 71 wt.%, leading to a yield of GP extract of 31 wt.%, and a yield of carbohydrates of 27 wt.%. The latter value corresponds to a recovery of approximately 84% of the total amount of carbohydrates (both soluble and structural) of GP, which indicates that the hydrolysis of cellulose occurred to some extent. Of the total amount of carbohydrates measured in the GP extract, approximately 80% were in the form of oligosaccharides. The most abundant monosaccharides in GP extract were glucose and fructose, which exist in GP as soluble carbohydrates, followed by arabinose, xylose and galactose, from hemicellulose. With a view to breaking down the oligosaccharides in the liquors produced in the SBW treatment, Viscozyme, an enzyme complex exhibiting cellulase and hemicellulase activity, was immobilized on glutaraldehyde-activated chitosan microparticles. The yield of enzyme immobilization was approximately 79%, and the enzyme kept about 75% of its specific activity, as determined in the hydrolysis of a model substrate (arabinogalactan). The enzymatic hydrolysis of GP and GP residue left in the reactor after SBW treatment was found to be very slow. That of GP extract was carried out but HPLC analysis was inconclusive. GP extract was used as carbon source for the growth of two oleaginous yeasts: Rhodotorula babjevae, and Lipomyces starkeyi. A comparative analysis of biomass and lipid production was made, in media with different pH and composition. Similar results were found with media at pH 4 and pH 6. Lipomyces starkeyi exhibited both highest cell dry weight and lipids dry weight in both the control medium (9.6 g/L cells, of which 5.3 g/L were lipids) containing glucose as carbon source, and medium with GP extract (0.9 g/L cells, of which 0.2 g/L are lipids) containing carbohydrates in an amount identical to that of glucose in the control medium. R. babjevae produced the highest carotenoid content, reaching 6.3 mg carotenoids / g cell dry weight in control assays with glucose.